Experimental study on salt weathering of sandstone with different weathering degrees - Yun Dong; Ningbo Peng; Jie Hong; Hengrui Liu; Le Tang; Bo Sun (Journal of Asian Architecture and Building Engineering, 2024)
Due to lithological and environmental differences, the weathering degree of stone heritage varies even within the same area. Various factors dominate the weathering process at different stages. Implementing preventive measures has reduced the impact of controllable factors such as human activities. However, salt weathering caused by atmospheric pollutants, water, and salt migration in rock formations has emerged as a major contributor to the deterioration of stone heritage. Understanding the re-weathering characteristics of stone cultural heritage at different weathering degrees is crucial for preventive protection. This study investigated the weathering status of Nanshiku Temple and designed an experimental scheme based on field monitoring data. By controlling the number of freeze-thaw cycles, stones with different weathering degrees were prepared, and sulfate weathering simulations were conducted. The results revealed severe damage to sandstone due to Na2SO4 crystallization. Higher initial weathering degrees resulted in more pronounced deterioration and faster weathering rates. Surface hardness analysis approximated the decay process using a logarithmic function within a certain range but could not fully capture the overall weathering of the stone. Uniaxial compressive strength showed a strong correlation with weathering indices like p-wave velocity. These findings provide a theoretical basis for preventive protection efforts in stone cultural heritage.